The Impact of Service Quality, Subjective Norms, and Voluntariness on Acceptance of Provider's Mobile Telecommunication Service in Jordan - Abdul Malek, A. Tambi; Abdul Aziz, Abdullah; Puspa Liza, Ghazali (2018)
Technology has made life easier in today’s world. In addition, developments in technologies and communication have become commonplace for majority of people. Global telecommunication development has reduced distances around the globe, and made it easy for businesses to proliferate worldwide. This study explored the factors affecting the use of telecommunication services among customers through mobile phones. The Technology Acceptance Model (TAM) has been extensively used in the field of technology use but is lacking when it comes to factors that affect customers’ intention to use service as they focus more on technology. On the basis of review findings, there is a positive relationship between service quality, subjective norms, perceived usefulness and perceived ease of use of service and voluntariness moderates the relationship between subjective norms and intention to use service. These and other relationships are considered in the development of a Service Acceptance Model.